Genetic variation of rs7958311 in P2X7R gene is associated with the susceptibility and disease activity of ankylosing spondylitis. Issue 1123 (16th April 2019) - Pan, Zhipeng; Zhang, Xu; Ma, Yubo; Xu, Shengqian; Shuai, Zongwen; Pan, Faming; Sun, Guoping
Abstract: Objectives: To describe association between the genetic variation of inflammation-associated gene, P2X7R, and ankylosing spondylitis (AS) susceptibility. Methods: Four single nucleotide polymorphisms (SNPs) of P2X7R gene were genotyped in 673 patients with AS and 687 healthy controls. Allele and genotype frequencies and different genetic models were performed to calculate ORs and 95% CIs, the demographic and clinical characteristics of patients were recorded. The data analyses were also conducted by sex. Results: Compared with controls, genetic variation in rs7958311 but not the other three SNPs was statistically significant in female patients (χ 2 =6.907, p=0.032). Specifically, the P2X7R gene rs7958311 polymorphism A allele showed a protective effect in AS susceptibility (OR=0.704, p=0.049, pFDR =0.061). In addition, female individuals with GA and/or AA genotypes had a lower risk of having AS compared with those with GG genotype (GA vs GG: OR=0.446, p=0.012, pFDR =0.030; AA vs GG: OR=0.440, p=0.039, pFDR =0.061; GA/AA vs GG: OR=0.445, p=0.009, pFDR =0.030). Furthermore, individuals with A allele (ie, GA/AA vs GG) had a higher disease activity, including Bath Ankylosing Spondylitis Disease Activity Index (overall: Z=− 2.630, p=0.014; male: Z=− 2.243, p=0.025), Schober test (overall: Z=− 3.041, p<0.001; male: Z=− 2.243, p=0.025) and chest expansion (overall: Z=− 3.895, p=0.004; male: Z=− 2.403, p=0.016). Conclusion: The allelic variation of rs7958311 SNP in P2X7R gene may have a protective effect on AS susceptibility in females and is associated with disease activity in male patients.